Do group interventions help people with autism spectrum disorder to develop better relationships with others? A critical review of the literature. (19th December 2018) - Atkinson‐Jones, Katherine; Hewitt, Olivia
Accessible summary: Lots of people with autism find it difficult to make friends and have relationships. There are lots of different groups that can help people with autism to learn social skills and how to make friends. Some of the groups were specially designed for people with a learning disability as well as autism. The groups can help support people to talk about their emotions, talk to other people about their thoughts and feelings and practise talking to other people. This paper found that social skills groups can help people with autism to improve their social skills and to talk to people more. The PEERS‐YA group appears to be the best social skills group for people with autism without a learning disability. More research is needed to learn more about social skills groups for people with autism and a learning disability. Abstract: Background: Social and communication impairments are a core diagnostic feature of autism spectrum disorder (ASD) and can act as a barrier to developing relationships. The National Institute for Health and Care Excellence (2016) guidelines recommend group social skills interventions as the first‐line treatment to help adults with ASD improve their social skills and relationships. To date, reviews have only explored the impact of group social skills interventions for adults with ASD without intellectual disability (ID). This review aimed to critically appraise studies investigating group social skills interventions for adults with ASD both without intellectual disability and with a mild or moderate intellectual disability. Method: A systematic search of four databases (PsycINFO, MEDLINE, EMBASE and CINAHL), as well as hand‐searching of references, was conducted. Ten studies were identified, employing different designs and methodologies, and covering six different group social skills interventions. Results: Overall, the review provided fairly consistent evidence that group social skills in different formats can reduce social impairments and increase social interaction, social knowledge and empathy for adults with ASD. Conclusion: There was variation in the quality of studies, and the most robust evidence was provided for the efficacy of the PEERS‐YA intervention. There was less evidence supporting the effectiveness of group social skills interventions for adults with ASD and intellectual disability, and more research is needed in this area.